Justification of placement of technical stations depending on the number of half-routes - Sattorov S.B. (Научно-технический вестник Брянского государственного университета)
Transport and the market are inseparable, interconnected. Their interaction accelerates the development of each of them and thereby the entire economy. In the modern world, timely delivery of goods, the delivery of goods to the cargo owner within the specified period determines the level of development and economic stability of the state. The work and equipping of technical stations, their location in the railway network affects the delivery time of the goods. Often, train locomotives do not fulfill their assigned tasks due to the lack of time for the locomotive crew in order to deliver the train to the nearest technical station, as well as the irrational use of the standard time of the locomotive crew. In connection with the expectation of delivery, the locomotive brigade replacing the locomotive, the idle time of the wagons at the intermediate stations increases. All this makes it difficult to control the movement of trains and reduces the speed of moving cars on the railway transport. The purpose of the study is to develop a method for placing technical stations on a railway test site in the course of an electric traction. To achieve this goal, it will be necessary to solve the following tasks: generalization of the main parameters of the location of technical stations; determination of half-races between technical stations in the operation of one locomotive brigade; search for the required number of change of the locomotive brigade; determination of the distance between technical stations. The methods of research are based on the generalization and analysis of existing results in finding the rational location of technical stations. It is revealed that the first step for the rational placement of technical stations is to determine the traction arm of the locomotive. When determining the length of the traction arm, the ways of using the locomotive for the duration of working time by one locomotive crew are considered. The rational placement of technical stations according to the proposed methodology will ensure the advancement of trains with the least number of parking lots for the replacement of locomotives, locomotive crews and inspection of rolling stock.